Особливості унормування (конституювання) принципів територіального устрою в Республіці Польща - Марчук, М. І.; Marchuk, M. I.; Марчук Микола Іванович (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 3 (70). - С. 30-37., 2015)
Зазначено, що для політико-територіальної організації Республіки Польща суттєве значення мають три види територіального поділу – базовий (загальний), допоміжний і спеціальний, наявність яких лише підкреслює децентралізований характер організації території цієї європейської держави. Підкреслено, що прийняті парламентом країни закони передбачають цілий ряд гарантій унітарного характеру польської держави, таких як єдина й однорідна правова система, єдине громадянство, єдність системи державної влади тощо. Наголошено, що принцип гарантування місцевого самоврядування є однією з ключових засад територіальної організації публічної влади у Республіці Польща. Зроблено висновок про подібність систем конституційних принципів територіального устрою Республіки Польща та України, що свідчить про певну єдність у розумінні конституційно-правових засад територіального устрою серед науковців обох країн.

It is indicated that three kinds of territorial division – basic (general), supplementary and special are essential for the political and territorial organization of the Republic of Poland. Their presence just emphasizes the decentralized nature of the organization of the territory of this European state It is also pointed out that local self-government units of the Republic of Poland, even those that are formed at the highest level of territorial division, have no attributes specific for a federal state or a state having autonomous regions. It stressed that adopted laws by the country’s Parliament provide a series of guarantees of the unitary character of the Polish state, such as a common and uniform legal system, a single citizenship and a unity in the system of state power, etc. It is summarized that the balance and the socio-economic development of regions in the Republic of Poland is achieved through implementation of European standards of regional development, the most important of which is the NUTS 2 level. It is concluded that the systems of constitutional principles of territorial structure of the Republic of Poland and Ukraine are quite similar, which indicates on a certain unity in the understanding of the constitutional and legal bases of the territorial structure amongst the scholars of both countries; specific for Poland dualistic model of governance at the regional level can be implemented in Ukraine under the delimitation of the powers of local authorities and local self-governments.

Указано, что для политико-территориальной организации Республики Польша существенное значение имеют три вида территориального деления – базовый (общий), вспомогательный и специальный, наличие которых лишь подчёркивает децентрализованный характер организации территории этого европейского государства. Подчёркнуто, что принятые парламентом страны законы предусматривают целый ряд гарантий унитарного характера польского государства, таких как единая и однородная правовая система, единое гражданство, единство системы государственной власти и т. п. Приведены аргументы, что принцип обеспечения местного самоуправления является одной из ключевых основ территориальной организации публичной власти в Республике Польша. Сделан вывод о сходстве систем конституционных принципов территориального устройства Республики Польша и Украины, что свидетельствует об определённом единстве в понимании конституционно-правовых основ территориального устройства среди учёных обеих стран.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Польща; Республіка Польща; територіальний устрій; унітаризм; децентралізація; місцеве самоврядування; публічна влада; Republic of Poland; Poland; territorial structure; unitarianism; decentralization; local self-government; public power; территориальное устройство; унитаризм; децентрализация; местное самоуправление; публичная власть; Польша; Україна. Ukraine. Украина